Characteristics and Outcome at 1 Month of Olfactory Dysfunction in Hospitalized COVID-19 Patients in a Tertiary Care Hospital (Journal of Dhaka Medical College, 2025)
Background: Olfactory dysfunction (OD) is well-established and is a key symptom of COVID-19 Although ample data are available regarding olfactory dysfunction in non-hospitalized COVID- 19 patients, there are knowledge gaps about the frequency, severity, and duration of OD in hospitalized COVID-19 patients. So, we conducted the study to determine the outcome of olfactory dysfunction in hospitalized patients with COVID-19.Methodology: This was a hospital-based prospective cohort study conducted in Dhaka Medical College and Hospital. RT-PCR-positive COVID-19 patients who matched the inclusion and exclusion criteria were enrolled in the study. A visual analog scale (VAS, 0-10 cm) assessed the severity of olfactory dysfunction. All the patients were followed up by telephonic interviews on the 10th and 30th day after the onset of olfactory dysfunction to assess the outcome of olfactory dysfunction. Olfactory-specific quality of life (QOL) was assessed in those patients who did not recover olfactory function completely at the 30th day follow-up.Results: We enrolled 277 patients in this study. A total of 90(32%) had olfactory dysfunction. Hyposmia was the most common type of olfactory dysfunction (54.22%), followed by anosmia (40.96%), hyperosmia, and parosmia (2.41%). The Mean age (SD) of the study subjects was 51.8(14.8) years, and the mean age(SD) of the patients with olfactory dysfunction and without olfactory dysfunction was (51.06[10.01]and 52.17[15.34]) years, respectively(p>0.05). there was no gender discrepancies between the groups (50[60.24%] vs 112[59.89%], p>0.05). The majority (53.7%) of the study subjects had severe COVID-19 infection, but olfactory dysfunction was more common among mild COVID-19 patients. In 85.54% of cases, Olfactory dysfunction was associated with taste dysfunction and/or headache. Olfactory dysfunction was completely resolved in 46.99% of cases within 10 days and 87.95% within 30 days. Median (IQR) recovery time from olfactory dysfunction was 14.00 (11.00) days; Recovery time was significantly more in severe COVID-19 patients than in mild COVID-19 patients (p